Ginger extract as green corrosion inhibitor of mild steel in hydrochloric acid solution - Fidrusli, Azreen; Suryanto, Suryanto; Mahmood, Mahmood Hameed (Institute of Physics, 2017)
Ginger extract as corrosion inhibitor from natural resources was studied to prevent corrosion of mild steel in acid media. Ginger rhizome was extracted to produce green corrosion inhibitor (G-1) while ginger powder bought at supermarket was also extract to form green corrosion inhibitor (G-2). Effectiveness of inhibitor in preventing corrosion process of mild steel was studied in 1.0 M of hydrochloric acid. The experiment of weight loss method and polarization technique were conducted to measure corrosion rate and inhibition efficiency of mild steel in solution containing 1.0 M of hydrochloric acid with various concentration of inhibitor at room temperature. The results showed that, the rate of corrosion dropped from 8.09 mmpy in solution containing no inhibitor to 0.72 mmpy in solution containing 150g/l inhibitor while inhibition efficiency up to 91% was obtained. The polarization curve in polarization experiments shows that the inhibition efficiency is 86% with high concentration of inhibitor. The adsorption of ginger extract on the surface of mild steel was observed by using optical microscope and the characterization analysis was done by using pH measurement method. When high concentration of green inhibitor in the acid solution is used, the pH at the surface of steel is increasing.